The Influence of Learning Independence and Learning Motivation on the Learning Outcomes of Buddhist Religion of Private High School Students in Medan Kota District - Albert, Albert; Elbistian, Kevin Putra; Prasetio, Meriyawaty Amelia; William, Justin Sebastian; Angkasa, Marco; Lowins, Leandro (Utan Kayu Publishing, 2025)
Education is a central point in efforts to prepare quality human resources. Whatever the activities carried out, essentially aims to always improve the quality of life or human welfare, individually or for all members of the community. One indicator of the success of the teaching and learning process is shown by the results of student evaluations. In learning and learning activities involve elements, namely, teachers, students, facilities and processes of learning and learning itself. In the learning process, the success of students in learning is influenced by innovative learning models. This study uses quantitative research methods. The research method used is a causal survey method with correlation techniques. The empirical data collected consisted of two independent variables, namely Learning Independence (X1), Learning Motivation (X2) and the dependent variable, namely Learning Outcomes (Y). Data collection techniques in quantitative research use a questionnaire developed through the indicators of each variable. The total number of population members is 3,239 people. The number of samples was obtained using the Slovin formula. So the minimum sample size in this study was 97 students from a population of 3,239 respondents with a significance level (?) of 10%. The results showed that the correlational hypothesis of the three variables was confirmed. It can be concluded that (1) There is a positive influence between Learning Independence (X1) on Learning Outcomes (Y) The results of hypothesis testing the effect of Learning Independence (X1) on Student Learning Outcomes (Y) with the regression equation = 22.241 + 0.792 X1, linear ( straight line), as evidenced by the linearity test. (2) There are results of hypothesis testing the effect of Learning Motivation (X2) on Students' Learning Outcomes (Y) with the regression equation = 23.197 + 0.799 X2, linear (straight line), (3) There is an Influence of Learning Independence (X1), Learning Motivation (X2) together on Learning Outcomes (Y). The results of hypothesis testing the effect of Learning Independence (X1), Learning Motivation (X2) together on Student Learning Outcomes (Y) with the regression equation = 22.484 + 1.837 X1 – 0.497 X2.